Preparation method and application of MXene / UiO-66-NH2 / PEI / MS composite adsorption material
By preparing a two-dimensional transition metal carbon-nitride/amino modified zirconium-based metal organic framework frame/polyethyleneimine coated melamine sponge composite adsorption material, the problem of removing europium in wastewater is solved, and efficient adsorption and reusable material are achieved.
Patent Information
- Application Number
- CN202510110137.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to effectively remove the radionuclide europium (Eu(III)) in wastewater, and traditional composite adsorbent materials have challenges in recycling and reuse.
The two-dimensional transition metal carbon-nitride/amino modified zirconium-based metal organic framework frame/polyethyleneimine coated melamine sponge (MXene/UiO-66-NH2/PEI/MS) composite adsorption material is used to enhance the chemical stability and recycling of the material by loading melamine sponge as the base material.
It realizes efficient adsorption and removal of Eu(III) in wastewater, and the material has good chemical stability and recycling, reducing environmental pollution and production costs.
Smart Images

Figure CN119897074A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a two-dimensional transition metal carbon-nitride / amino-modified zirconium-based metal organic framework / polyethyleneimine-coated melamine sponge (MXene / UiO-66-NH2 / PEI / MS) composite adsorption material, belonging to the technical field of wastewater treatment. Background Art
[0002] As the country's requirements for clean energy continue to increase, the nuclear energy industry has grown rapidly, and nuclear power has become an important source of stable, safe, low-cost and reliable basic electricity, and can reduce carbon emissions. However, the development of the nuclear energy industry has brought about the impact of heavy metal pollutants on the environment, such as radioactive wastewater generated by nuclear fuel preparation, isotope production, mineral mining and processing. The wastewater generated by these activities contains a variety of radioactive nuclides, which pose a serious threat to the environment and human health, damage aquatic ecosystems, and may even cause radiation poisoning, cancer, genetic diseases and other effects.
[0003] Europium (Eu) is widely present in the fission products of nuclear fuel control materials and is considered to be a chemical homologue of trivalent lanthanide elements with similar adsorption properties. Due to the long-term radioactive hazards and various adverse effects of Eu(III)-containing pollutants, even at extremely low levels, they can pose a serious threat to ecological aquatic organisms and public health through the food chain, such as organ damage, acute radiation syndrome, leukemia, kidney damage, nervous system diseases, cardiovascular system damage, cancer and even death. Therefore, removing and purifying radioactive nuclei Eu(III) from wastewater is of great scientific significance.
[0004] Two-dimensional transition metal carbon-nitride (MXene) is a new type of two-dimensional material with a graphene-like structure. The preparation of MXene by etching with lithium fluoride (LiF) and hydrochloric acid (HCl) system will make its surface carry functional groups such as −OH, −F and −O, so it shows great potential in the field of pollutant treatment. However, due to the poor chemical properties of MXene, its performance is greatly reduced when used as a composite adsorbent. Metal organic frameworks (MOFs) usually use inorganic metal atoms, ions and metal clusters as coordination centers, and are combined with single or multiple organic ligands through a variety of coordination methods. UiO-66 is a metal organic framework with zirconium (Zr) as the metal center and terephthalic acid (BDC) as the organic ligand. Due to its excellent stability, large specific surface area, high porosity, and coordination, it is modified by introducing amino (-NH2) groups on the basis of UiO-66 to obtain specific catalytic and adsorption properties. However, it is easy to cause environmental pollution during preparation and use.
[0005] Therefore, the present invention proposes a two-dimensional transition metal carbon-nitride / amino-modified zirconium-based metal organic framework / polyethyleneimine-coated melamine sponge (MXene / UiO-66-NH2 / PEI / MS) composite adsorption material, which has a good effect on the removal of Eu(III) in wastewater. Summary of the invention
[0006] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to use materials with high porosity and rich surface functional groups for loading, to prepare new nanomaterials, to explore and prepare a MXene / UiO-66-NH2 / PEI / MS composite porous nano-adsorption material with safe, efficient enrichment performance and reusability, and to apply it as a new adsorbent material to actual large-scale wastewater treatment.
[0007] The present invention provides a method for preparing a two-dimensional transition metal carbon-nitride / amino-modified zirconium-based metal organic framework / polyethyleneimine-coated melamine sponge (MXene / UiO-66-NH2 / PEI / MS) composite adsorbent material, using melamine sponge (MS) as a base material, and loading the other three materials onto MS, so as to facilitate the recovery and reuse of the composite material; polyethyleneimine (PEI) is used to enhance the chemical stability of MXene, so that MXene can show its excellent performance in the composite adsorbent material, and polyethyleneimine (PEI) is an aliphatic polymer with strong chelating and biocompatibility, and a large number of amino groups on the macromolecular chain have chelating effects on heavy metals, so that it has good heavy metal adsorption performance. Compared with the traditional preparation method, the UiO-66-NH2 preparation method mentioned in the present invention can reduce the intermediate products that pollute the environment. By combining the above materials, a composite adsorbent material with a large specific surface area, rich surface functional groups and stable chemical structure is formed, which has great adsorption potential for radioactive nuclide europium (Eu). At present, there are difficulties in the recovery process of the composite adsorbent material in powder form after the adsorption is completed. Therefore, the present invention loads the three materials on MS with the characteristics of high porosity, non-toxicity, hygiene and environmental protection, which is convenient for the recycling of the composite adsorbent material and makes the composite adsorbent material have better economic benefits and practical use value.
[0008] The present invention provides a method for preparing a MXene / UiO-66-NH2 / PEI / MS composite adsorption material. Melamine sponge (MS) is used as a substrate material, PEI / MS is obtained by an immersion method, and MXene is prepared by etching with an HCl and LiF system. The surface of the MXene / UiO-66-NH2 has −OH, −F and −O functional groups, and the MXene / UiO-66-NH2 has a large pore structure and a high specific surface area, which significantly increases the adsorption performance of heavy metal ions. Finally, MXene / UiO-66-NH2 is loaded on PEI / MS by dopamine hydrochloride (PDA), and the defect of easy oxidation of MXene is improved by the excellent chemical properties of polyethyleneimine (PEI), so as to obtain MXene / UiO-66-NH2 / PEI / MS with excellent adsorption performance.
[0009] The above preparation method specifically comprises the following steps: S1: Preparation of PEI / MS: ultrasonically washing melamine sponge (MS) in ethanol and deionized water, respectively, and drying; soaking the cleaned melamine sponge in a polyethyleneimine aqueous solution (PEI), stirring, and drying to obtain PEI / MS; S2: Preparation of MXene: Lithium fluoride (LiF) and concentrated hydrochloric acid (HCl) are placed in a reactor and stirred slowly; titanium aluminum carbide (Ti3AlC2) is slowly added to the reactor in small amounts; dilute hydrochloric acid is first added to the product after the reaction to clean the unreacted LiF, and then deionized water is added to wash, and the operation is repeated to make the pH ≥ 6; MXene is obtained by precipitation and drying; S3: Preparation of MXene / UiO-66-NH2: Add zirconium n-propoxide (Zr(OCH2CH2CH3)4) solution to a mixed solution of N,N-dimethylformamide (DMF) and glacial acetic acid (HAC) in a volume ratio of 2:1, add the MXene prepared in step S2 to the above solution, and ultrasonically oscillate until dispersed, then dissolve 2-aminoterephthalic acid (BDC-NH2) in the above mixed solution, fully dissolve and transfer to a reactor for hydrothermal reaction; after naturally cooling to room temperature, wash the precipitate with DMF and methanol; finally, dry the obtained solid to obtain MXene / UiO-66-NH2; S4: Preparation of MXene / UiO-66-NH2 / PEI / MS: Disperse dopamine hydrochloride (PDA) and the MXene / UiO-66-NH2 prepared in step S3 in Tris-HCl buffer; immerse the PEI / MS prepared in step S1 in the solution and slowly stir at room temperature; then wash with distilled water and dry to obtain MXene / UiO-66-NH2 / PEI / MS.
[0010] Further, in step S1, the MS is ultrasonicated in ethanol and deionized water for 30 to 60 minutes, the mass percentage of the polyethyleneimine aqueous solution is 1%, the immersion time is 30 to 45 minutes, the drying temperature is 60 to 65° C., and the drying time is 12 to 24 hours.
[0011] Further, in step S2, the mass ratio of LiF to Ti3AlC2 is 1.2-2.0:1, the dosage is 0.6-5.0 g and 0.5-2.5 g respectively, the concentration of concentrated hydrochloric acid is 9-12 mol / L, the mass ratio of Ti3AlC2 to concentrated hydrochloric acid is 1 g:10-30 mL, the concentration of dilute hydrochloric acid is 1-2 mol / L. The reaction temperature is 35-45°C, and the reaction time is 24-48 h.
[0012] Further, in step S3, the molar ratio of Zr(OCH2CH2CH3)4 and BDC-NH2 is 1:0.7~1.2, the dosage is 0.3~0.7g and 0.1~0.5g respectively, the volume ratio of methanol and DMF is 2:1, and the molar ratio of HAC and Zr(OCH2CH2CH3)4 is 15:1. The concentration of MXene suspension is 5~10 g / L. The hydrothermal reaction temperature is 120℃, and the reaction time is 20~24 h. The precipitation drying temperature is 80~90℃.
[0013] Further, in step S4, the mass ratio of PDA and MXene / UiO-66-NH2 is 1:1, the concentration of Tris-HCl buffer is 10 mmol / L, and the pH is 8.5; the amount of Tris-HCl buffer is 20-100 mL. The stirring speed is 200-500 rpm / min, and the stirring time is 12-15 h. The drying temperature is 60-65 ° C, and the drying time is 12-15 h.
[0014] The present invention provides a MXene / UiO-66-NH2 / PEI / MS composite adsorption material prepared by the above preparation method.
[0015] The present invention provides an application of the above-mentioned two-dimensional transition metal carbon-nitride / amino-modified zirconium-based metal organic framework / polyethyleneimine-coated melamine sponge (MXene / UiO-66-NH2 / PEI / MS) composite adsorption material, and the above-mentioned composite adsorption material is used to remove Eu(III) in wastewater.
[0016] The specific application process is as follows: by adding the prepared Eu(III) stock solution and NaNO3 background ion solution into a centrifuge tube to simulate the relevant pollution environment, then adjusting the solution to the required pH value by NaOH and HNO3, and finally putting the above-mentioned MXene / UiO-66-NH2 / PEI / MS composite adsorption material into it for oscillation adsorption for 24 hours to complete the adsorption process; after the adsorption process is completed, the centrifuge tube is centrifuged and the supernatant is taken, and the remaining Eu(III) ion concentration is determined by ultraviolet spectrophotometer.
[0017] Beneficial effects of the present invention: (1) In the present invention, the metal organic framework material UiO-66-NH2 is composed of a zirconium (Zr) metal center and a 2-aminoterephthalic acid (BDC-NH2) organic ligand with a -NH2 functional group. This structure is formed by a [Zr6O4(OH)4] metal cluster coordinated with 12 ligands under ideal conditions. With dense structural units and a strong affinity between zirconium (Zr) and oxygen (O), a strong Zr-O bond is formed. By introducing amino (-NH2) groups on the basis of UiO-66 for modification, specific catalytic and adsorption properties are obtained. The introduction of NH2 not only increases the chemical functionality of UiO-66-NH2, but also may enhance its ability to interact with other molecules. UiO-66-NH2 has a large pore structure and a high specific surface area, which makes it show a wide range of application potential in the fields of catalysis, adsorption and separation. At the same time, by using zirconium n-propoxide Zr(OCH2CH2CH3)4 to synthesize UiO-66-NH2, no HCl will be produced as in the traditional synthesis using zirconium chloride (ZrCl4), which reduces the pollution of the intermediate product to the environment and is more environmentally friendly.
[0018] (2)MXene is a new type of two-dimensional material with a graphene-like structure. It is composed of transition metal carbides, nitrides or carbonitrides. Its unique two-dimensional layered structure can not only increase the surface area and provide more active sites, but also promote the diffusion and adsorption of heavy metal ions inside the material. At the same time, the large interlayer spacing of MXene is conducive to the entry of heavy metal ions into the interlayer region, thereby increasing the adsorption rate. The preparation of MXene by LiF and HCl system etching will cause its surface to carry functional groups such as -OH, -F and -O, which can interact with heavy metal ions and improve adsorption performance.
[0019] (3) Polyethyleneimine (PEI) is an organic polymer containing primary amine, secondary amine and tertiary amine groups. It is a positively charged aliphatic polymer with strong chelating properties, hydrophilicity, biocompatibility and a large number of amino groups on the macromolecular chain. Due to the chelating effect of its amine functional groups on heavy metal cations and heavy metal cluster anions, it has good heavy metal adsorption performance. At the same time, PEI has good chemical stability, which can increase the stability of the composite adsorption material.
[0020] (4) Melamine sponge (MS) has the characteristics of high specific surface area and rich pore structure, which is conducive to mass transfer and adsorption of adsorbents. It has good flexibility and plasticity, and can be prepared into adsorbent materials of different shapes and sizes as needed. In addition, the surface is rich in nitrogen atoms and ammonium ions, and selective adsorption of specific substances can be achieved by changing its surface functional groups. When used as a base adsorbent material, MS has a high adsorption capacity and adsorption rate, and can quickly adsorb target substances. It has good chemical stability and durability, and can be reused many times without losing adsorption performance. At the same time, MS has low cost, simple preparation and operation, and is suitable for large-scale applications.
[0021] (5) The present invention uses MXene / UiO-66-NH2 / PEI / MS composite material as an adsorbent to adsorb Eu(III) in sewage, and has achieved good results. The four materials, MXene, UiO-66-NH2, PEI and MS, will produce complementary and enhanced performance through synergistic effects, which will enhance the adsorption performance of radioactive nuclides Eu(III) while making up for the defects of the single materials themselves. The high conductivity and mechanical strength of MXene can improve the overall electron transmission capacity of the composite material; the high porosity of UiO-66-NH2 is conducive to improving the adsorption performance of the composite adsorbent material; the application of PEI not only provides more amino functional groups for the composite adsorbent material, enhances the chelation effect on radioactive nuclides, but also improves the defect of MXene's easy oxidation, and further enhances the mechanical strength and stability of the material; MS as a base material can provide a good support structure and rich pore size, which is also convenient for the recovery and reuse of the composite adsorbent material; the four materials can cooperate with each other through reasonable loading and combination, and have broad application prospects in energy storage, water treatment, environmental purification and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the MXene / UiO-66-NH2 / PEI / MS composite adsorption material of Example 1 of the present invention; Figure 2 This is a Fourier transform infrared spectrum of the MXene / UiO-66-NH2 / PEI / MS composite adsorption material of Example 1 of the present invention; Figure 3 The effect of pH on the adsorption of Eu(III) on the MXene / UiO-66-NH2 / PEI / MS composite adsorption material when the background ion is 0.001 mol / L NaNO3 in Example 2 of the present invention; Figure 4 The effect of pH on the adsorption of Eu(III) on the MXene / UiO-66-NH2 / PEI / MS composite adsorption material when the background ion is 0.01 mol / L NaNO3 in Example 3 of the present invention; Figure 5 The effect of pH on the adsorption of Eu(III) on the MXene / UiO-66-NH2 / PEI / MS composite adsorption material when the background ion is 0.10 mol / L NaNO3 in Example 4 of the present invention; Figure 6 The effect of pH on the adsorption of Eu(III) on the MXene / UiO-66-NH2 / PEI / MS composite adsorption material when the background ion is 0.001 mol / L NaCl in Example 5 of the present invention; Figure 7 The effect of pH on the adsorption of Eu(III) on the MXene / UiO-66-NH2 / PEI / MS composite adsorption material when the background ion is 0.001 mol / L Na2SO4 in Example 6 of the present invention; Figure 8 The effect of the MXene / UiO-66-NH2 / PEI / MS composite adsorption material on the adsorption of Eu(III) with different initial concentrations at 30°C in Example 7 of the present invention; Fig. 9 The effect of the MXene / UiO-66-NH2 / PEI / MS composite adsorption material on the adsorption of Eu(III) with different initial concentrations at 45°C in Example 8 of the present invention; Fig.10 The effect of the MXene / UiO-66-NH2 / PEI / MS composite adsorption material on the adsorption of Eu(III) with different initial concentrations at 60°C in Example 9 of the present invention; Fig.11 This is the effect of different MXene / UiO-66-NH2 / PEI / MS concentrations on the adsorption of Eu(III) in Example 10 of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further illustrated by the following examples, but is not limited to the following examples. Example 1
[0024] This embodiment provides a method for preparing a two-dimensional transition metal carbon-nitride / amino-modified zirconium-based metal organic framework / polyethyleneimine-coated melamine sponge composite adsorption material, comprising the following steps: S1 Preparation of PEI / MS: Wash MS by ultrasonic in ethanol and deionized water for 45 min respectively, take it out and dry it in a 65°C drying oven; dissolve PEI in deionized water to make a 1% (w / w) solution, immerse the washed MS in it, stir for 1 h, take it out and dry it in a 70°C drying oven to obtain PEI / MS.
[0025] S2 Preparation of MXene: 1.6 g LiF and 20 mL 12 M HCl were placed in a reactor and stirred at 40 °C for 15 min. 1 g Ti3AlC2 was slowly added to the reactor in small amounts and reacted at 40 °C for 48 h. After the reaction, it was washed with 2 M HCl 2 to 3 times, then washed with deionized water until the pH of the upper liquid was ≥ 6, and dried in a drying oven at 80 to 90 °C to obtain MXene.
[0026] Among them, the mass ratio of LiF and Ti3AlC2 is 1.6:1, and the ratio of the mass of Ti3AlC2 and the volume of 12M HCl is 1g:20mL.
[0027] S3 preparation of MXene / UiO-66-NH2: 0.327g Zr(OCH2CH2CH3)4 was mixed with 25mL DMF, 5mL HAC and 12.5mL methanol, the MXene prepared in S2 was dispersed in deionized water, a MXene suspension with a concentration of 10 g / L was prepared and added to the above mixed solution for ultrasonic oscillation; 0.181g BDC-NH2 was dissolved in the above mixed solution, and after it was fully dissolved, it was transferred to a reactor for hydrothermal reaction at 120°C; after naturally cooling to room temperature, it was washed with DMF and methanol for 2 to 3 times respectively; the obtained solid was placed in a drying oven at 85 to 95°C and dried for 12h to obtain MXene / UiO-66-NH2.
[0028] Among them, the molar ratio of Zr(OCH2CH2CH3)4 and BDC-NH2 is 1:1, the molar ratio of methanol and DMF is 2:1, and the molar ratio of HAC and Zr(OCH2CH2CH3)4 is 15:1.
[0029] Preparation of MXene / UiO-66-NH2 / PEI / MS in S4: 100 mg PDA and 100 mg MXene / UiO-66-NH2 prepared in S3 were dispersed in 50 mL Tris-HCl buffer with a concentration of 10 mmol / L and a pH of 8.5; PEI / MS prepared in S1 was immersed in it and slowly stirred at room temperature for 12 h with a magnetic stirring speed of 200~400 rpm / min; it was washed with distilled water three times and dried in a drying oven at 65~75℃ for 12 h to obtain MXene / UiO-66-NH2 / PEI / MS.
[0030] Among them, the mass ratio of PDA and MXene / UiO-66-NH2 is 1:1.
[0031] The results of morphological characterization of the obtained MXene / UiO-66-NH2 / PEI / MS composite material by scanning electron microscopy (SEM) are shown in Figure 1 As shown, the left and right sides represent scanning electron microscope images at different magnifications of 200 μm and 2 μm, respectively. Figure 1 , it was observed that the MXene / UiO-66-NH2 / PEI / MS composite material maintained a complete melamine sponge skeleton structure, and there were adhesions between the pores, which were speculated to be polyethyleneimine coated on the melamine sponge. At the same time, polyethyleneimine and dopamine hydrochloride can help MXene and UiO-66-NH2 attach to the melamine sponge. Multilayer flakes and regular octahedral structures were observed on the adhesions and sponge skeletons, which are consistent with the structure of two-dimensional transition metal carbon-nitride MXene and amino-modified zirconium-based metal organic framework UiO-66-NH2, which is MXene / UiO-66-NH2. It can be inferred from SEM characterization that MXene / UiO-66-NH2 / PEI / MS is a preliminary successful composite; Figure 2 This is the Fourier transform infrared spectrum of MXene / UiO-66-NH2 / PEI / MS. Figure 2 From the infrared spectrum, we can see that at a wavelength of 1565 cm -1 The absorption peak represents the stretching oscillation of asymmetric NH at a wavelength of 1108 cm -1 The absorption peak represents the stretching oscillation of CH, which is the characteristic peak of PEI. -1 The absorption peak at 660 cm represents the stretching vibration of the 1,3,5-triazine ring, which is formed due to the incomplete carbonization of MS. -1 The absorption peak represents the stretching oscillation of Ti-O at a wavelength of 1260 cm -1 represents the stretching vibration of CF at a wavelength of 3448 cm-1 Represents the stretching vibration of hydroxyl groups. All of the above are characteristic peaks of MXene; at a wavelength of 475 cm -1 and 766 cm -1 The absorption peak represents the stretching vibration of O-Zr-O at a wavelength of 1380 cm -1 represents the symmetric vibration of -COOH at a wavelength of 1495 cm -1 The absorption peak represents the stretching oscillation of C=O in the ligand, at a wavelength of 1660 cm -1 Represents the stretching vibration of residual C=O in DMF. All of the above are characteristic peaks of UiO-66-NH2.
[0032] In summary, it shows that the preparation of MXene / UiO-66-NH2 / PEI / MS composites is successful.
[0033] In this embodiment, MXene, UiO-66-NH2 and PEI with excellent adsorption performance are loaded onto MS with high specific surface area, rich pore structure and easy recovery, and a safe, environmentally friendly, efficient enrichment performance and reusable MXene / UiO-66-NH2 / PEI / MS composite material is prepared, which significantly increases the adsorption performance of the material for heavy metal ions. Therefore, on the whole, the preparation steps of MXene / UiO-66-NH2 / PEI / MS composite materials are environmentally friendly, green and pollution-free from the perspective of recycling, the materials are all renewable resources, and can be solved in complex sewage environment treatment. The above fully illustrates its good performance and unique advantages, and it has broad prospects in the field of industrial sewage.
[0034] The following comparative examples illustrate the limitations of the MXene / UiO-66-NH2 / PEI / MS composite material not prepared by the method of the present invention.
[0035] Comparative Example 1 This example provides a method for preparing a MXene / UiO-66-NH2 / PEI / MS composite material, comprising the following steps: S1 Preparation of PEI / MS: Wash MS by ultrasonic in ethanol and deionized water for 30-60 min respectively, take it out and dry it in a drying oven at 60-70°C; dissolve PEI in deionized water to make a 1% (w / w) solution, immerse the washed MS in it, stir for 1 h, take it out and dry it in a drying oven at 65-75°C to obtain PEI / MS.
[0036] S2 Preparation of MXene: 1.6 g LiF and 20 mL 12 M HCl were placed in a reactor and stirred at 40 °C for 15 min. 1 g Ti3AlC2 was slowly added to the reactor in small amounts and reacted at 40 °C for 48 h. After the reaction, it was washed with 2 M HCl for 2 to 3 times and then with deionized water until the pH of the upper liquid was ≥ 6. The precipitate was dispersed in 45 mL deionized water and ultrasonicated in an ice bath for 1 h in a nitrogen environment. The upper liquid was dried in a drying oven at 80 to 90 °C to obtain a single-layer MXene.
[0037] S3 preparation of MXene / UiO-66-NH2: 0.327g Zr(OCH2CH2CH3)4 was mixed with 25mL DMF, 5mL HAC and 12.5mL methanol, the MXene prepared in S2 was dispersed in deionized water, a MXene suspension with a concentration of 10 g / L was prepared and added to the above mixed solution for ultrasonic oscillation; 0.181g BDC-NH2 was dissolved in the above mixed solution, and after it was fully dissolved, it was transferred to a reactor for hydrothermal reaction at 120°C; after naturally cooling to room temperature, it was washed with DMF and methanol for 2 to 3 times respectively; the obtained solid was placed in a drying oven at 85 to 95°C and dried for 12h to obtain MXene / UiO-66-NH2.
[0038] Among them, the molar ratio of Zr(OCH2CH2CH3)4 and BDC-NH2 is 1:1, the molar ratio of methanol and DMF is 2:1, and the molar ratio of HAC and Zr(OCH2CH2CH3)4 is 15:1.
[0039] Preparation of MXene / UiO-66-NH2 / PEI / MS by S4: 100 mg PDA and 100 mg MXene / UiO-66-NH2 prepared in S3 were dispersed in 50 mL Tris-HCl buffer with a concentration of 10 mmol / L and a pH of 8.5; PEI / MS prepared in S1 was immersed in the solution and slowly stirred at room temperature for 12 h with a magnetic stirring speed of 200~400 rpm / min; it was washed with distilled water three times and dried in a drying oven at 65~75℃ for 12 h to obtain MXene / UiO-66-NH2 / PEI / MS.
[0040] Among them, the mass ratio of PDA and MXene / UiO-66-NH2 is 1:1.
[0041] Compared with Example 1, when preparing MXene in step S2 of this comparative example, a single layer of MXene is prepared by ice bath ultrasound in a nitrogen environment, and the same subsequent preparation steps are used. The results show that although the SEM performance of the single layer MXene is more intuitive, because it is more easily oxidized in the environment, the content of the single layer MXene obtained after vacuum drying is less; and in the process of preparing MXene / UiO-66-NH2, the adhesion effect of UiO-66-NH2 and the single layer MXene is not good. It is speculated that it is also because the single layer MXene is oxidized in the subsequent experimental operation, affecting the content in the composite adsorption material, thereby directly affecting the composite material for The adsorption effect of radioactive nuclides Eu (III). Therefore, the use of multilayer MXene can not only increase the yield, but also reduce the impact of its oxidation during the subsequent preparation process, that is, the method in Example 1. The results show that the improved method of the present invention is feasible.
[0042] Comparative Example 2 S1 Preparation of PEI / MS: Wash MS by ultrasonic in ethanol and deionized water for 30-60 min respectively, take it out and dry it in a 60-70°C drying oven; dissolve PEI in 1% (w / w) deionized water, immerse the washed MS therein, stir for 1 h, take it out and dry it in a 65-75°C drying oven to obtain PEI / MS.
[0043] S2 Preparation of MXene: 1.6 g LiF and 20 mL 12 M HCl were placed in a reactor and stirred at 40 °C for 15 min. 1 g Ti3AlC2 was slowly added to the reactor in small amounts and reacted at 40 °C for 48 h. After the reaction, it was washed with 2 M HCl 2 to 3 times, then washed with deionized water until the pH of the upper liquid was ≥ 6, and dried in a drying oven at 80 to 90 °C to obtain MXene.
[0044] Among them, the mass ratio of LiF and Ti3AlC2 is 1.6:1, and the mass ratio of Ti3AlC2 and 12M HCl is 1g:20mL.
[0045] Preparation of MXene / UiO-66-NH2 / PEI / MS by S3: 0.327 g Zr(OCH2CH2CH3)4 was mixed with 25 mL DMF, 5 mL HAC and 12.5 mL methanol; the MXene prepared in S2 was dispersed in deionized water to prepare a MXene suspension with a concentration of 10 g / L and then added to the above mixed solution for ultrasonic oscillation; 0.181 g BDC-NH2 was dissolved in the above mixed solution and transferred to the reactor after being fully dissolved; the PEI / MS prepared in S1 was immersed in the solution in the reactor and subjected to hydrothermal reaction at 120 °C; after naturally cooling to room temperature, it was washed with DMF and methanol for 2 to 3 times respectively; the obtained solid was placed in a drying oven at 85 to 95 °C and dried for 12 h to obtain MXene / UiO-66-NH2 / PEI / MS.
[0046] Among them, the molar ratio of Zr(OCH2CH2CH3)4 and BDC-NH2 is 1:1, the molar ratio of methanol and DMF is 2:1, and the molar ratio of HAC and Zr(OCH2CH2CH3)4 is 15:1.
[0047] Compared with Example 1, in this comparative example, it is expected that MXene / UiO-66-NH2 / PEI / MS is prepared in one step by the hydrothermal method shown in step S3, but the experimental results show that the product in the reactor loses the physical morphology of MS, and MS changes from a cubic structure of 1cm×1cm×1cm at the beginning of the experiment to irregular small blocks, causing the composite adsorbent material to lose the characteristics of MS as a base material and can no longer be easily recycled. Therefore, the experimental steps of preparing MXene / UiO-66-NH2 / PEI / MS composite adsorbent material in one step by hydrothermal method are improved, first preparing MXene / UiO-66-NH2 by hydrothermal method, and then loading MXene / UiO-66-NH2 with PEI / MS by PDA, that is, the method in Example 1. The results show that the improved method of the present invention is feasible.
[0048] The present invention also discloses an application of a MXene / UiO-66-NH2 / PEI / MS composite material, and the specific application process is as follows: according to the influencing factors studied in different embodiments, a prepared Eu(III) stock solution and a NaNO3 background ion solution are added to a centrifuge tube to simulate a related polluted environment, and then the pH value of the mixed solution is adjusted by NaOH and HNO3, and finally, the adsorption material MXene / UiO-66-NH2 / PEI / MS is added for oscillation adsorption for 24 hours to complete the adsorption process; after the adsorption process is completed, the centrifuge tube is centrifuged and the supernatant is taken, and the remaining Eu(III) ion concentration is determined by an ultraviolet spectrophotometer.
[0049] The present invention is further described in detail in specific embodiments below with reference to Examples 2 to 10 in combination with the accompanying drawings and the influence of background ions NaNO3 of 0.001 mol / L to 0.10 mol / L on the adsorption effect, the influence of different background ions NaCl and Na2SO4 at a concentration of 0.001 mol / L on the adsorption effect, and the study of the adsorption effect of materials under the environments of 30°C, 45°C and 60°C.
[0050] Table 1 Parameters in various embodiments Example 2
[0051] In this example, the temperature is 30 °C, the concentration of the adsorbent MXene / UiO-66-NH2 / PEI / MS is 0.667 g / L, and the concentration of Eu(III) is 9.87×10 5 mol / L and the background ion was 0.001 mol / L NaNO3, the adsorption rate of Eu(III) by the MXene / UiO-66-NH2 / PEI / MS composite material prepared in Example 1 was studied at different pH values.
[0052] The experimental results are as follows Figure 3 As shown in the figure, the adsorption rate of Eu(III) by MXene / UiO-66-NH2 / PEI / MS composite material is the lowest at pH 2, about 50%. As the pH increases, the adsorption rate of Eu(III) by the material gradually increases, reaching a maximum adsorption rate of about 74% at pH 2 to 8. As the pH continues to increase, the adsorption efficiency of the material is basically stable at about 73%. This is because when the pH is lower than 3, Eu in water is mainly in the form of Eu 3+ and EuNO3 2+ At this time, the surface of the MXene / UiO-66-NH2 / PEI / MS composite material is in a positive charge state, and the electrostatic repulsion with the pollutants in the water is strong, repelling each other and almost no reaction occurs, resulting in a low adsorption rate; when the pH rises to 8, the surface of the material is negatively charged, and Eu in the water 3+ Gradually converted into Eu(CO3) + and EuOH 2+ , and gradually dominates. At this time, the attraction between positive and negative charges increases, so the adsorption rate of the material for Eu(III) gradually increases; when the pH increases from 8 to 11, the surface of the material shows a deprotonation phenomenon. At this time, different types of europium carbonate in the aqueous solution, such as Eu(CO3)2 - 、EuHCO3 2+ 、Eu(CO3) +The deprotonated material surface produces a strong complexation reaction, which enhances the adsorption rate of Eu(III) by the adsorbent material and gradually maintains a stable state.
[0053] Example 3 In this example, the temperature is 30 °C, the concentration of the adsorbent MXene / UiO-66-NH2 / PEI / MS is 0.667 g / L, and the concentration of Eu(III) is 9.87×10 -5 mol / L and the background ion was 0.01 mol / L NaNO3, and the adsorption rate of the MXene / UiO-66-NH2 / PEI / MS composite material prepared in Example 1 at different pH values was studied.
[0054] The experimental results are as follows Figure 4 As shown in the figure, the adsorption rate of Eu(III) by MXene / UiO-66-NH2 / PEI / MS composite material is the lowest at pH 2, which is about 45%. As the pH increases, it gradually increases to the maximum adsorption efficiency at pH 2 to 8, which is about 72%, and as the pH continues to increase, the adsorption efficiency of Eu(III) by the material is basically stable at about 70%.
[0055] Example 4 In this example, the temperature is 30 °C, the concentration of the adsorbent MXene / UiO-66-NH2 / PEI / MS is 0.667 g / L, and the concentration of Eu(III) is 9.87×10 -5 mol / L and the background ion was 0.10 mol / L NaNO3, the adsorption rate of the MXene / UiO-66-NH2 / PEI / MS composite material prepared in Example 1 at different pH values was studied.
[0056] The experimental results are as follows Figure 5 As shown in the figure, the adsorption rate of Eu(III) by MXene / UiO-66-NH2 / PEI / MS composite material is the lowest at pH 2, which is about 38%. As the pH increases, the adsorption efficiency gradually rises to a maximum of about 68% at pH 2 to 8. As the pH continues to increase, the adsorption efficiency is basically stable at about 68%, tending to be stable.
[0057] The analysis of the adsorption efficiency and pH changes under different ion backgrounds shows that the adsorption rate is the lowest when pH is 2. As the pH gradually increases, the adsorption rate also gradually increases. In particular, it gradually increases to the maximum adsorption efficiency when pH is 2 to 8. As the pH continues to increase, the adsorption efficiency generally tends to be stable and basically stabilizes at around the maximum adsorption efficiency. The influence of ion background is also particularly important. When the ion background is 0.001 mol / L, the ion effect is the lowest, and the adsorption rate is also the highest at about 74%. When the ion background is 0.10 mol / L, the ion effect is the highest, and the maximum adsorption rate is only 68%.
[0058] Example 5 In this example, the temperature is 30 °C, the concentration of the adsorbent MXene / UiO-66-NH2 / PEI / MS is 0.667 g / L, and the concentration of Eu(III) is 9.87×10 -5 mol / L and the background ion was 0.001 mol / L NaCl, the effect of the MXene / UiO-66-NH2 / PEI / MS composite material prepared in Example 1 on the adsorption rate at different pH values was studied.
[0059] The experimental results are as follows Figure 6 As shown in the figure, the adsorption rate of Eu(III) by MXene / UiO-66-NH2 / PEI / MS composite material is as low as about 48% at pH 2. When the pH is 2-8, the adsorption efficiency gradually increases to about 74%. As the pH continues to increase, the adsorption efficiency of the material for Eu(III) stabilizes at about 73%, tending to be stable.
[0060] Example 6 In this example, the temperature is 30 °C, the concentration of the adsorbent MXene / UiO-66-NH2 / PEI / MS is 0.667 g / L, and the concentration of Eu(III) is 9.87×10 -5 mol / L and the background ion was 0.001 mol / L Na2SO4, and the effect of the MXene / UiO-66-NH2 / PEI / MS composite material prepared in Example 1 on the adsorption rate at different pH values was studied.
[0061] The experimental results are as follows Figure 7 As shown in the figure, the adsorption rate of Eu(III) by MXene / UiO-66-NH2 / PEI / MS composite material is as low as about 40% at pH 2, and rises to a maximum of about 67% at pH 2 to 8. As the pH continues to increase, the adsorption efficiency gradually tends to be stable at 8 to 11, and its adsorption rate is stable at about 67%.
[0062] Based on Example 1, Example 5 and Example 6, the influence of different ion backgrounds on adsorption is quite different. Especially under the condition of Na2SO4, the average adsorption efficiency of the material is the lowest, and the maximum adsorption efficiency is only about 67%. It is speculated that this may be due to the sulfate ion (SO4 2- ) easily combines with europium ions in the solution to form sulfate products, which makes it difficult for the material to bind to its adsorption sites, and reduces the free europium ions in the solution, making the adsorption sites more difficult to complex and adsorb. At the same time, sulfate (SO4 2- ) will react with the positive charges of the MXene / UiO-66-NH2 / PEI / MS composite material, reducing the efficient active binding sites and further reducing the adsorption behavior.
[0063] Example 7 In this example, the MXene / UiO-66-NH2 / PEI / MS composite prepared in Example 1 was studied at a temperature of 30°C (303 K), an adsorbent concentration of 0.667 g / L, a solution pH of 6.0, and a background ion of 0.001 mol / L NaNO3 to investigate the adsorption of MXene / UiO-66-NH2 / PEI / MS composite materials in the presence of 3.95×10 -5 mol / L to 1.51×10 -3 mol / L effect on the adsorption of Eu(III) at different initial concentrations; The experimental results are as follows Figure 8 As shown in Figure 2, the adsorption process is relatively slow, and the initial concentration changes from low to high. The lowest initial concentration is 3.95×10 -5 mol / L, the highest initial concentration was 1.51×10 -3 mol / L. Among them, C e represents the concentration of the remaining metal ions at equilibrium, q e It indicates the adsorption capacity of the remaining metal ions at equilibrium. The adsorption rate is low when the initial concentration is the lowest, and the adsorption capacity is about 2.68×10 -5 mol / g, and then its adsorption capacity gradually increased with the increase of concentration, and the maximum adsorption capacity was about 6.59×10 -4 mol / g, and the change tends to equilibrium. The reason why it can maintain a good adsorption rate at a high initial concentration of Eu(III) is that under the condition of high concentration of Eu(III), the adsorption binding sites increase and there will be a stronger ion driving force until the adsorption equilibrium is reached.
[0064] Example 8 In this example, the MXene / UiO-66-NH2 / PEI / MS composite prepared in Example 1 was studied at a temperature of 45°C (318 K), an adsorbent concentration of 0.667 g / L, a solution pH of 6.0, and a background ion of 0.001 mol / L NaNO3 to investigate the adsorption of MXene / UiO-66-NH2 / PEI / MS composite materials in the presence of 3.95×10 -5 mol / L to 1.18×10 -3 mol / L effect on the adsorption of Eu(III) at different initial concentrations; The experimental results are as follows Fig. 9 As shown in Figure 2, the adsorption process is relatively slow, and the initial concentration changes from low to high. The lowest initial concentration is 3.95×10 -5 mol / L, the highest initial concentration was 1.18×10 -3 mol / L. Among them, C e represents the concentration of the remaining metal ions at equilibrium, q e It indicates the adsorption capacity of the remaining metal ions at equilibrium. The adsorption rate is low when the initial concentration is the lowest, and the adsorption capacity is about 1.06×10 -5 mol / g, and then its adsorption capacity gradually increased with the increase of concentration, and the maximum adsorption capacity was about 7.86×10 -4 mol / g. The reason why it can maintain a good adsorption rate at a high initial concentration of Eu(III) is attributed to the stronger ionic driving force of high concentration Eu(III) until the adsorption equilibrium is reached.
[0065] Example 9 In this example, the MXene / UiO-66-NH2 / PEI / MS composite prepared in Example 1 was studied at a temperature of 60°C (333 K), an adsorbent concentration of 0.667 g / L, a solution pH of 6.0, and a background ion of 0.001 mol / L NaNO3 to investigate the adsorption of MXene / UiO-66-NH2 / PEI / MS composite materials in the presence of 3.95×10 -5 mol / L to 1.05×10 -3 mol / L effect on the adsorption of Eu(III) at different initial concentrations; The experimental results are as follows Fig.10 As shown in Figure 2, the adsorption process is relatively slow, and the initial concentration changes from low to high. The lowest initial concentration is 3.95×10 -5 mol / L, the highest initial concentration was 1.05×10 -3 mol / L. Among them, C e represents the concentration of the remaining metal ions at equilibrium, qe It indicates the adsorption capacity of the remaining metal ions at equilibrium. The adsorption rate is low when the initial concentration is the lowest, and the adsorption capacity is about 3.01×10 -5 mol / g, and then its adsorption capacity gradually increased with the increase of concentration, and the maximum adsorption capacity was about 8.92×10 -4 mol / g.
[0066] Combining Examples 8, 9 and 10, it can be seen that as the experimental temperature increases, the adsorption amount increases accordingly. The increase is small at a lower initial concentration and obvious at a higher initial concentration, from 6.59×10 -4 mol / g increased to 8.92×10 at 60℃ -4 mol / g.
[0067] Example 10 This example studies the removal rate comparison of the MXene / UiO-66-NH2 / PEI / MS composite adsorbent prepared in Example 1 at different adsorbent material concentrations at a temperature of 30°C, a solution pH of 6.0, and a background ion of 0.001 mol / L NaNO3.
[0068] from Fig.11 It can be found that with the increase of adsorbent concentration, the adsorption rate of MXene / UiO-66-NH2 / PEI / MS composite material also increases. When the content of MXene / UiO-66-NH2 / PEI / MS composite material reaches 1.30 g / L, the removal rate reaches 72%, indicating that the higher porosity and abundant adsorption sites on the MXene / UiO-66-NH2 / PEI / MS composite material can provide great advantages.
[0069] In summary, the MXene / UiO-66-NH2 / PEI / MS composite material prepared in Example 1 has a fine microstructure, can provide a large adsorption amount and contact specific surface area, and has a large adsorption capacity for Eu(III). In addition, during the preparation process, the base material MS is green, environmentally friendly, inexpensive, and easy to recycle. The composite material can efficiently recycle pollutants and effectively recycle metals such as Eu, and can quickly and efficiently not cause secondary pollution to the environment. In addition, after compounding different metal organic framework materials, the selective adsorption of different pollutants can be enhanced, and it can be used for water treatment in different environments.
[0070] To further illustrate various embodiments, the present invention provides drawings. These drawings are part of the disclosure of the present invention, which are mainly used to illustrate the embodiments and can be used in conjunction with the relevant descriptions in the specification to explain the operating principles of the embodiments. With reference to these contents, ordinary technicians in this field should be able to understand other possible implementations and advantages of the present invention.
[0071] The above description is only a preferred embodiment of the present invention and is not a limitation on the design of this case. Any equivalent changes made based on the design key of this case shall fall within the protection scope of this case.
Claims
1. A method for preparing a MXene / UiO-66-NH2 / PEI / MS composite adsorption material, characterized in that: Using melamine sponge as the substrate material, PEI / MS was obtained by immersion method; MXene was prepared by etching with HCl and LiF system; MXene / UiO-66-NH2 was prepared by hydrothermal method; finally, MXene / UiO-66-NH2 was loaded on PEI / MS by dopamine hydrochloride to obtain MXene / UiO-66-NH2 / PEI / MS composite adsorption material with excellent adsorption performance.
2. The method for preparing the MXene / UiO-66-NH2 / PEI / MS composite adsorption material according to claim 1, characterized in that The steps include: S1: Preparation of PEI / MS: ultrasonically washing a melamine sponge in ethanol and deionized water, respectively, and drying; soaking the cleaned melamine sponge in a polyethyleneimine aqueous solution, stirring, and drying to obtain PEI / MS; S2: Preparation of MXene: lithium fluoride and concentrated hydrochloric acid are placed in a reactor and stirred slowly; titanium aluminum carbide is slowly added to the reactor in small amounts; after the reaction, dilute hydrochloric acid is first added to clean the unreacted LiF, and then deionized water is added to wash, and the operation is repeated to make the pH ≥ 6; MXene is obtained by precipitation and drying; S3: Preparation of MXene / UiO-66-NH2: Adding the zirconium n-propoxide solution to a mixed solution of N,N-dimethylformamide and glacial acetic acid in a volume ratio of 2:1, adding the MXene prepared in step S2 to the above solution, ultrasonically oscillating until dispersed to form a MXene suspension, and then dissolving 2-aminoterephthalic acid in the above mixed solution, fully dissolving and transferring to a reactor for hydrothermal reaction; after naturally cooling to room temperature, washing the precipitate with DMF and methanol; finally, drying the obtained solid to obtain MXene / UiO-66-NH2; S4: Preparation of MXene / UiO-66-NH2 / PEI / MS: Disperse dopamine hydrochloride and the MXene / UiO-66-NH2 prepared in step S3 in Tris-HCl buffer; immerse the PEI / MS prepared in step S1 in the solution and slowly stir at room temperature; then wash with distilled water and dry to obtain MXene / UiO-66-NH2 / PEI / MS.
3. The method for preparing the MXene / UiO-66-NH2 / PEI / MS composite adsorption material according to claim 2, characterized in that: In step S1, the MS is ultrasonicated in ethanol and deionized water for 30-60 min, the mass percentage of the polyethyleneimine aqueous solution is 1%, the soaking time is 30-45 min, the drying temperature is 60-65° C., and the drying time is 12-24 h.
4. The method for preparing the MXene / UiO-66-NH2 / PEI / MS composite adsorption material according to claim 2, characterized in that: In step S2, the mass ratio of LiF and Ti3AlC2 is 1.2~2.0:1, the dosage is 0.6~5.0g and 0.5~2.5g respectively, the concentration of concentrated hydrochloric acid is 9~12mol / L, the volume ratio of the mass of Ti3AlC2 and concentrated hydrochloric acid is 1g:10~30mL, and the concentration of dilute hydrochloric acid is 1~2 mol / L.
5. The method for preparing the MXene / UiO-66-NH2 / PEI / MS composite adsorption material according to claim 2, characterized in that: In step S2, the reaction temperature is 35-45° C. and the reaction time is 24-48 h.
6. The method for preparing the MXene / UiO-66-NH2 / PEI / MS composite adsorption material according to claim 2, characterized in that: In step S3, the molar ratio of Zr(OCH2CH2CH3)4 and BDC-NH2 is 1:0.7~1.2, the dosage is 0.3~0.7g and 0.1~0.5g respectively, the volume ratio of methanol and DMF is 2:1, the molar ratio of HAC and Zr(OCH2CH2CH3)4 is 15:1; the concentration of MXene suspension is 5~10 g / L.
7. The method for preparing the MXene / UiO-66-NH2 / PEI / MS composite adsorption material according to claim 2, characterized in that: In step S3, the hydrothermal reaction temperature is 120°C, the reaction time is 20-24 h, and the precipitation drying temperature is 80-90°C.
8. The method for preparing the MXene / UiO-66-NH2 / PEI / MS composite adsorption material according to claim 2, characterized in that: In step S4, the mass ratio of PDA and MXene / UiO-66-NH2 is 1:1, the concentration of Tris-HCl buffer is 10 mmol / L, and the pH is 8.5; the amount of Tris-HCl buffer is 20-100 mL, the stirring speed is 200-500 rpm / min, and the stirring time is 12-15 h; the drying temperature is 60-65 ° C, and the drying time is 12-15 h.
9. A MXene / UiO-66-NH2 / PEI / MS composite adsorption material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the MXene / UiO-66-NH2 / PEI / MS composite adsorption material according to claim 9 in removing Eu(III) from wastewater.
Citation Information
Cited By
Core-shell structure MOF material capable of selectively adsorbing rhenium and preparation method and application of rhenium adsorbing material
CN120939919A
MXene-coated UiO-66-coated PAP nano-composite, preparation method, flame-retardant composite and application
CN121450116A